2020
DOI: 10.1101/2020.08.06.239293
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased oscillatory power in a computational model of the olfactory bulb due to synaptic degeneration

Abstract: The olfactory bulb (OB) is one of the first regions of the brain affected by Parkinson’s disease (PD) as measured by both dysfunction and presence of α-synuclein aggregation. Better understanding of how PD affects OB function could lead to earlier diagnosis and potential treatment. By simulating damage to the OB in a computational model, it may be possible to identify regions of interest or markers of early disease. We modified a simple rate-based computational model of the olfactory bulb and simulated damage … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 109 publications
(239 reference statements)
0
1
0
Order By: Relevance
“… 188 , 190 Consistent with these findings, additional recent work in a biophysical model of the OB during seeding-like damage, reported that decreasing the strength of synaptic connections in the OB leads to an increase in the power of oscillatory rhythms. 20 , 193 Like the abnormal increase in beta-band activity observed in Parkinsonian individuals (described above), an increase in oscillations occurring as a consequence to α-syn aggregates could be detrimental to normal information processing of the OB and given the OB’s strong influence over down-stream connected structures (e.g. the amygdala, hippocampus) likely would impact other regions.…”
Section: Mechanisms Underlying Early Network Dysfunction: What We Kno...mentioning
confidence: 99%
“… 188 , 190 Consistent with these findings, additional recent work in a biophysical model of the OB during seeding-like damage, reported that decreasing the strength of synaptic connections in the OB leads to an increase in the power of oscillatory rhythms. 20 , 193 Like the abnormal increase in beta-band activity observed in Parkinsonian individuals (described above), an increase in oscillations occurring as a consequence to α-syn aggregates could be detrimental to normal information processing of the OB and given the OB’s strong influence over down-stream connected structures (e.g. the amygdala, hippocampus) likely would impact other regions.…”
Section: Mechanisms Underlying Early Network Dysfunction: What We Kno...mentioning
confidence: 99%